QUR'AN SMART SPEAKER WITH VOICE CONTROL USING RASPBERRY PI AND GOOGLE ASSISTANT LIBRARY - Kamel, Ahmad; Marindani, Elang Derdian; Sujaini, Herry (Faculty of Engineering, Universitas Tanjungpura, 2023)
Rapid technological developments have a significant impact on various aspects of life, making it easier and more efficient. Speech recognition enables control of devices without physical contact, as studied here. This research focuses on controlling voice with Raspberry Pi and Google Assistant to play audio Qur'an, meeting the needs of the Muslim community in Indonesia. Users can select and play Qur'an audio easily, saving time compared to manual selection. The research was conducted by designing the device and testing the performance and capabilities of the tool. Software as well as hardware is designed to achieve research objectives. The research findings show that the device functions properly according to design, controlled by voice. The average time for detecting a wake word is 0.86 seconds while recognizing commands takes an average time of 6.74 seconds. Microphones with amplifiers proved to be the most effective, suitable for control within a maximum of 1 meter, with a success rate of up to 80%. The device has a tolerable noise limit for voice command recognition, which is less than 60 dB. Future speech recognition system development should consider a low-noise environment for effective use. This research has the potential to improve audio players for Quran recitation and reduce reliance on traditional remote controls and heavy manuals, creating further opportunities in Muslim societies and globally.